The Used of Online Learning Method in Acquiring Children's English Vocabulary at English Buzz Bali - Masuci, Ni Putu Manik (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 21 No 2 (2021)DO - 10.24843/PJIIB.2021.v21.i02.p10, 2021)
This study entitled “The Used of Online Learning Method in Acquiring Children's English Vocabulary at English Buzz Bali”. It focuses on finding out the effectiveness of Online Learning Method in acquiring English vocabulary. This study was test how effective is the use of online learning method to teach children’s English Vocabulary at English Buzz Bali and to know the student perception about their new learning method of study. The research of this study applied field work research that used theories by Revan Revan (1991 in M. Pedlar edition (2011) about theory of action learning and Terry Anderson (2008) about online learning method. This research used teaching and observation technique involving students in the third grade of elementary school. The data in this study were the collected from the result of Pre-test and Post-test of the students of English Buzz Bali using online platform; ZOOM for their teaching and learning process. There were ten children (M= 9) participating in this study and official permission from the school has been obtained to conduct the study. The result of this study shows that, the use of online learning method is quite effective to acquiring English vocabulary for the children during the pandemic Covid-19.  It can be seen from the high percentage score (80,85%) of correct answer from the Post-test of the students who been taught through online platform.  It can be concluded that online learning method is the suggested ways to acquiring children’s English vocabulary during the pandemic Covid-19.